Chemical structure and impurities of catherers as a source of allergic reactions - Czernych, Radosław; Gałęzowska, Grażyna; Opalińska, Aleksandra; Bagniewski, Paweł; Wolska, Lidia (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Application of peripheral venous catherer is one of the most often carried out medical procedures. The procedure is based on introduction of extraneous element (catherer) into cardiovascular system. However, there is a small awareness of possible health effects directly connected with introducing chemical impurities adsorbed onto the surface of a catherer or the king of material the catherer is made of. Allergic reactions in form of nettle-rash or erythema occur most often. Nonetheless, there are also known case studies of anaphylactic shocks after application of catherers. Nursing Topics 2013; 21 (4): 91–98